The China–India–Pakistan Nuclear Triangle: Consequential Choices for Asian Security - Salman Bashir (Journal for Peace and Nuclear Disarmament, 2022)
Asia-Pacific is the new locus of global power politics. To contain the rise of China, India has joined the United States in shaping a “geo-political” response to China’s “geo-economic” outreach. A “maritime dimension” has been added to the complex “continental” contestations between India–China and India-Pakistan, injecting new risks of nuclear instability in the region. Responsibly managing competition is emerging as a key theme. India’s nuclear and military modernization programs are status driven. The Indo-US defence partnership has led to a worsening of India–China relations and disturbed the tenuous strategic balance between Pakistan and India. A nuclear conflict between China and India is unlikely. Nuclear risks in South Asia remain high. Conventional imbalance and Indian bellicosity have compelled Pakistan to develop a doctrine of “full-spectrum” credible minimum nuclear deterrence.